Extended Postnatal Brain Development in the Longest-Lived Rodent: Prolonged Maintenance of Neotenous Traits in the Naked Mole-Rat Brain - Orr, Miranda E.; Garbarino, Valentina R.; Salinas, Angelica; Buffenstein, Rochelle (Frontiers in Neuroscience, 2016)
The naked mole-rat (NMR) is the longest-lived rodent with a maximum lifespan >31 years. Intriguingly, fully-grown naked mole-rats (NMRs) exhibit many traits typical of neonatal rodents. However, little is known about NMR growth and maturation, and we question whether sustained neotenous features when compared to mice, reflect an extended developmental period, commensurate with their exceptionally long life. We tracked development from birth to three years of age in the slowest maturing organ, the brain, by measuring mass, neural stem cell proliferation, axonal and dendritic maturation, synaptogenesis and myelination. NMR brain maturation was compared to data from similar sized rodents, mice, and to that of long-lived mammals, humans and non-human primates. We found that at birth, NMR brains are significantly more developed than mice, and rather are more similar to those of newborn primates, with clearly laminated hippocampi and myelinated white matter tracts. Despite this more mature brain at birth than mice, postnatal NMR brain maturation occurs at a far slower rate than mice, taking four-times longer than required for mice to fully complete brain development. At four months of age, NMR brains reach 90% of adult size with stable neuronal cytostructural protein expression whereas myelin protein expression does not plateau until nine months of age in NMRs, and synaptic protein expression continues to change throughout the first three years of life. Intriguingly, NMR axonal composition is more similar to humans than mice whereby NMRs maintain expression of three-repeat (3R) tau even after brain growth is complete; mice experience an abrupt downregulation of 3R tau by postnatal day 8 which continues to diminish through six weeks of age. We have identified key ages in NMR cerebral development and suggest that the long-lived NMR may provide neurobiologists an exceptional model to study brain developmental processes that are compressed in common short-lived laboratory animal models.